Is Value Added Tax (VAT) Reform in India Poverty Improving? An Analysis Of Data From Five Major States - Poulomi Roy, Ajitava Raychaudhuri, Sudip Kumar Sinha (Indian Economic Review, 2010)
Value Added Tax (VAT) as introduced in India at state level from April 1, 2005 is widely acclaimed to be a better system than the sales tax on grounds of efficiency. However policy makers did not consider its impact on the distribution of income. Considering both the distributive and efficiency criteria we search for a poverty reducing direction of VAT reform in India. Conclusions reached from five major states in India, namely Gujarat, Karnataka, Madhya Pradesh, Maharashtra and West Bengal suggest that VAT reform is not largely poverty reducing. Further scopes of improvement in its design are observed.